Flow-controlled ventilation (FCV) improves regional ventilation in obese patients – a randomized controlled crossover trial - Weber, Jonas (BMC Anesthesiol, 2020)
BACKGROUND: In obese patients, high closing capacity and low functional residual capacity increase the risk for expiratory alveolar collapse. Constant expiratory flow, as provided by the new flow-controlled ventilation (FCV) mode, was shown to improve lung recruitment. We hypothesized that lung aeration and respiratory mechanics improve in obese patients during FCV. METHODS: We compared FCV and volume-controlled (VCV) ventilation in 23 obese patients in a randomized crossover setting. Starting with baseline measurements, ventilation settings were kept identical except for the ventilation mode related differences (VCV: inspiration to expiration ratio 1:2 with passive expiration, FCV: inspiration to expiration ratio 1:1 with active, linearized expiration). Primary endpoint of the study was the change of end-expiratory lung volume compared to baseline ventilation. Secondary endpoints were the change of mean lung volume, respiratory mechanics and hemodynamic variables. RESULTS: The loss of end-expiratory lung volume and mean lung volume compared to baseline was lower during FCV compared to VCV (end-expiratory lung volume: FCV, − 126 ± 207 ml; VCV, − 316 ± 254 ml; p < 0.001, mean lung volume: FCV, − 108.2 ± 198.6 ml; VCV, − 315.8 ± 252.1 ml; p < 0.001) and at comparable plateau pressure (baseline, 19.6 ± 3.7; VCV, 20.2 ± 3.4; FCV, 20.2 ± 3.8 cmH(2)O; p = 0.441), mean tracheal pressure was higher (baseline, 13.1 ± 1.1; VCV, 12.9 ± 1.2; FCV, 14.8 ± 2.2 cmH(2)O; p < 0.001). All other respiratory and hemodynamic variables were comparable between the ventilation modes. CONCLUSIONS: This study demonstrates that, compared to VCV, FCV improves regional ventilation distribution of the lung at comparable PEEP, tidal volume, P(Plat) and ventilation frequency. The increase in end-expiratory lung volume during FCV was probably caused by the increased mean tracheal pressure which can be attributed to the linearized expiratory pressure decline. TRIAL REGISTRATION: German Clinical Trials Register: DRKS00014925. Registered 12 July 2018.